Penerapan Customer Relationship Management Terhadap Minat Menginap Kembali Tamu Di Alila Hotel SCBD - Kevin, Kevin; Iskandar, Hari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the implementation of Customer Relationship Management (CRM) and its impact on the intention of guests to stay again at Alila Hotel SCBD. The theoretical foundation is based on Ripa Ioan Alexandru & Reinartz et al., who state that CRM can enhance customer loyalty through improved satisfaction and long-term relationships. The research method used is quantitative with purposive sampling technique. Data were collected through questionnaires distributed to 373 respondents who were guests of Alila Hotel SCBD. The margin of error applied in this study is 5%, according to the Slovin formula. The results of the study show that the implementation of CRM at Alila Hotel SCBD has a significant impact on guests' intention to stay again. Data analysis revealed that customer satisfaction and the quality of the relationship between guests and the hotel are the main factors influencing guest loyalty. The study also found that improving CRM implementation can increase the number of guests intending to stay again. The conclusion of this study is that CRM is an effective strategy in increasing guests' intention to stay again at Alila Hotel SCBD. It is recommended that hotel management continue to develop and improve their CRM systems to ensure better guest satisfaction and loyalty in the future.